Sistem Informasi dan Analisis Data Curah Hujan Kota Bandar lampung - Zakaria, Ahmad; Didik, Didik; Algifari, Habib (UNIVERSITAS LAMPUNG, 2013)
Hydrological data especially rainfall data that observed, often not available, in the otherwords there are missing data. Unavailability of complete data becomes an important prob-lem for the next data processing. Lost data will reduce information that consist in data.There is no a media service access on collect rainfall data with easily and quickly becomes ahomework that must be completed. For help access and processing rainfall data, it's impor-tant to developed